2022
DOI: 10.1177/10499091211068824
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Features and Factors Associated With Do-Not-Resuscitate Consent in Advanced Cancer Patients Admitted to Palliative Care Ward

Abstract: This study aimed to conduct a retrospective cross-sectional study to investigate the prevalence of symptoms and symptom clusters on sociodemographic and disease characteristics, as well as factors associated with Do-Not-Resuscitate (DNR) consent. Advanced cancer patients were enrolled between 2018 and 2020 with available data. Demographic and clinical data were obtained for analysis from Hospital Information System (HIS) in China. Symptom clusters were extracted by hierarchical cluster analysis. Chi-square tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 79 publications
(103 reference statements)
0
4
0
Order By: Relevance
“…The search strategy identified 8697 references, although only 131 full text articles were retrieved ( Figure 1 ). Twenty-six studies were identified during the initial database searches [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]; three further studies were identified during the re-searches in June 2023 [ 40 , 41 , 42 ]. The studies identified included 26 prognostication studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The search strategy identified 8697 references, although only 131 full text articles were retrieved ( Figure 1 ). Twenty-six studies were identified during the initial database searches [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]; three further studies were identified during the re-searches in June 2023 [ 40 , 41 , 42 ]. The studies identified included 26 prognostication studies [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , …”
Section: Resultsmentioning
confidence: 99%
“…The three non-prognostic studies also involved variable/limited numbers of patients (median: 102; range: 30–798) [ 35 , 36 , 42 ]. Pearse et al only assessed blood pressure [ 35 ], and this was measured on admission to the hospice.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations